Continental vs. Insular: Demographic and Growth Patterns in Acanthodactylus schreiberi - Büşra Kara; Mehmet Zülfü Yıldız; Deniz Yalçınkaya; Abdullah Altunışık (Animals)
This study examines the demographic parameters, body size, survival rates, and growth dynamics of Acanthodactylus schreiberi populations in continental (Botaş, Türkiye) and insular (Dipkarpaz, Northern Cyprus) habitats to understand how ecological constraints influence life-history traits. By integrating skeletochronological and morphometric analyses, we identified significant interpopulation differences. The continental population exhibited broader age ranges, higher survival rates, and less restricted growth, likely due to greater resource availability. In contrast, the insular population showed life-history variations associated with limited resources, including smaller body sizes, lower survival rates, and distinct growth patterns. Sexual dimorphism was more pronounced in the insular population, with males exhibiting higher growth rates. These findings suggest that habitat size, resource availability, and isolation shape demographic and morphological traits, highlighting the evolutionary and ecological pressures in different environments. The results underscore the need for conservation strategies tailored to these unique populations, particularly in the face of environmental changes.